The Post-Quarantine Economic Reactivation Environmental and Social Challenges - Gamboa Balbín, César Leonidas (2020)
The COVID-19 pandemic has generated a humanitarian and economic crisis globally, and especially Peru has been hit by this virus. After the quarantine finished (July first), the new normal has imposed new rules of coexistence, such as social distancing. Simultaneously, under pressure from various economic key-actors, the Peruvian Government has been promoting an economic reactivation plan in 4 controlled phases to accelerate economic growth that has fallen by 15% of GDP for the next five years. However, this economic reactivation plan has a potential cost on the investments' environmental and social impacts. In this sense, we will analyze how the antecedents of economic recovery plans (2013), the political context in which we live, and the new legal framework and proposed regulations can contribute to a more significant environmental and social impact. We will not only show that they have a normative inconsistency with the rule that preceded them, but that there is no certainty of the effectiveness of their mission to be able to reactivate the Peruvian economy from sustainability criteria and a human rights approach.